Mothers of a Child with Cerebral Palsy: Perception on the Diagnosis Moment and the Child's General and Oral Health - Flavia Rabello; Heloisa Vieira Prado; Gabriela Lopes Angelo; Milene Bento Martins; Natália Cristina Ruy Carneiro; Ana Cristina Borges-Oliveira (Association of Support to Oral Health Research (APESB), 2021)
Objective: To analyze the perception of mothers of children with Cerebral Palsy (CP) on the diagnosis moment and the child's health. Material and Methods: Research with a qualitative approach, carried out with 19 mothers of children with CP, in a public higher education institution, in the state of Minas Gerais, Brazil. For data collection, the interview was used and for data interpretation, content analysis. Results: Mothers reported that the diagnosis of a child with CP resulted in major changes in the family's daily life, increasing their responsibility and demands. After the diagnosis, mothers revealed oscillating feelings, with progressively replaced by her motherly ability to take care, reestablishing the psychic balance. The health associated with the absence of disease and curative practices was frequently observed. Mothers reported a great concern with oral hygiene habits and frequent visits to the dentist. Conclusion: The diagnosis of a child with CP led to changes in the family's priorities and routine. After the moment of anguish, uncertainty and fear, the mothers accepted the reality. The biomedical principle significantly influenced the mother´s perception of health, being health perceived as the absence of disease and curative practices. In relation to oral health, practices widely spread and recommended by the media and health services, such as correct tooth brushing, showed an orientation of patients to maintain oral health.